Methane-Derived Authigenic Carbonates on the Seafloor of the Laptev Sea Shelf - Kravchishina, Marina D.; Lein, Alla Yu; Flint, Mikhail V.; Baranov, Boris V.; Miroshnikov, Alexey Yu; Dubinina, Elena O.; Dara, Olga M.; Boev, Andrey G.; Savvichev, Alexander S. (Frontiers in Marine Science, 2021)
Seafloor authigenic carbonate crusts are widespread in various oceanic and marine settings, excluding high-latitude basins that are corrosive to carbonate precipitation. Newly formed carbonate formations are relatively rare in modern Arctic marine sediments. Although the first-order principles of seep carbonate formation are currently quite well constrained, little is known regarding the duration or mode of carbonate formation in the Siberian Arctic shelf. Large (massive slabs or blocks) and small crusts that were micrite cemented have been recently discovered on the seafloor of the Siberian Arctic seas within the area of known seep activity in the outer Laptev Sea shelf. Cold methane seeps were detected in the area due to the presence of an acoustic anomaly in the water column (gas flares). Microbial mats, methane gas bubbles, and carbonate crusts were observed using a towed camera platform. Here, we report new geochemical and mineralogical data on authigenic shallow Siberian Arctic cold-seep carbonate crusts to elucidate its genesis. The Laptev Sea carbonate crusts mainly consist of high-Mg calcite (up to 23 mol % MgCO3). The δ13C values in carbonates range significantly (from –40.1 to –25.9‰ VPDB), while the δ18O values vary in a narrow range (+4.4 ± 0.2‰ VPDB). The δ13C values of Corg that was determined from carbonates range from –40.2 to –31.1‰ VPDB. Using the isotope data and taking into account the geological setting, we consider that not only microbial but possibly thermogenic methane participated in the authigenic carbonate precipitation. Carbonate crust formation occurred below the water/sediment interface of the shallow Siberian Arctic shelf as a result of gas hydrate dissociation during Holocene warming events. The studied carbonate crusts were exhumated after precipitation into shallow subsurface shelf sediments.